Estrategia educativa en salud oral: Camaleón sonriente cuida tus dientes para niños de las comunidades indígenas Awá, Ico Valle de Anape, y Resguardo indígena Nasa Páez Huila (2022)
According to WHO (2020), oral diseases affect 3.5 billion people and therefore constitute an important burden for the health sector. Objective: To evaluate the effectiveness of an educational strategy called smiling chameleon take care of your teeth in children aged 6 to 12 years in indigenous communities Awá, Ico valley of Anape and Nasa Páez Huila indigenous re servation. Materials and methods: It is a longitudinal study, through which the application of the strategy "Smiling Chameleon takes care of your teeth" is carried out. Results: positive impacts were identified in variables such as use of toothbrush, denta l floss and frequency of brushing posttest. Conclusions: With respect to the plaque index applied the educational strategy of evidence an improvement in the index which is validated in that p value is less than 0.05 which indicates the effectiveness of the strategy.